Sex differences in TGFB-β signaling with respect to age of onset and cognitive functioning in schizophrenia - Frydecka D (Dove Medical Press, 2015)
Dorota Frydecka,1 Błazej Misiak,1,2 Edyta Pawlak-Adamska,3 Lidia Karabon,3,4 Anna Tomkiewicz,3 Paweł Sedlaczek,5 Andrzej Kiejna,1 Jan Aleksander Beszłej1 1Department of Psychiatry, Wroclaw Medical University, Wroclaw, Poland; 2Department of Genetics, Wroclaw Medical University, Wroclaw, Poland; 3Laboratory of Immunopathology, Department of Experimental Therapy, Institute of Immunology and Experimental Therapy, Polish Academy of Sciences, Wroclaw, Poland; 4Department of Clinical Urology, Wroclaw Medical University, Wroclaw, Poland; 51st Department and Clinic of Gynecology and Obstetrics, Wroclaw Medical University, Wroclaw, Poland Abstract: There are studies showing that gene polymorphisms within the transforming growth factor-β (TGF-β) signaling constitute schizophrenia risk variants. However, the association between TGFB1 gene polymorphisms (+869T/C and +915G/C), TGF-β level with schizophrenia course, and its symptomatology together with cognitive functioning has not been investigated so far. We included 151 patients with schizophrenia and 279 healthy controls. Cognitive functioning was assessed using Rey Auditory Verbal Learning Test, Trail Making Test (TMT)-A and TMT-B, Verbal Fluency task, Stroop test, as well as selected subtests from the Wechsler Adults Intelligence Scale – Revised, Polish adaptation (WAIS-R-Pl): Digit Symbol Coding, Digit Span Forward and Backward, and Similarities. Additionally, serum TGF-β levels were measured in 88 schizophrenia patients and 88 healthy controls. Serum TGF-β level was significantly higher among patients with schizophrenia in comparison with healthy controls; however, the studied polymorphisms were not associated with TGF-β level in schizophrenia patients. Subjects carrying the +869T allele performed significantly worse in comparison with +869CC homozygotes on Stroop task, Verbal Fluency task and Digit Symbol Coding task. There was a significant difference in age of psychosis onset in female schizophrenia patients with respect to the TGFB1 +869T/C polymorphism. Additionally, adjustment for possible confounders revealed that there was a significant difference in cognitive performance on Digit Symbol Coding task with respect to the TGFB1 +869T/C polymorphism among female schizophrenia patients. Our results suggest that TGF-β signaling might be a valid link contributing to observed differences in age of onset and the level of cognitive decline between male and female schizophrenia patients. Keywords: cognition, digit symbol coding task, gender differences, gene polymorphism, TGF, transforming growth factor-beta